Conformational Plasticity of Hepatitis C Virus Core Protein Enables RNA-Induced Formation of Nucleocapsid-like Particles - Holmstrom, Erik D.; Nettels, Daniel; Schuler, Benjamin (Journal of molecular biology, 2018)
Many of the unanswered questions associated with hepatitis C virus assembly are related to the core protein (HCVcp), which forms an oligomeric nucleocapsid encompassing the viral genome. The structural properties of HCVcp have been difficult to quantify, at least in part because it is an intrinsically disordered protein. We have used single-molecule Förster Resonance Energy Transfer techniques to study the conformational dimensions and dynamics of the HCVcp nucleocapsid domain (HCVncd) at various stages during the RNA-induced formation of nucleocapsid-like particles. Our results indicate that HCVncd is a typical intrinsically disordered protein. When it forms small ribonucleoprotein complexes with various RNA hairpins from the 3′ end of the HCV genome, it compacts but remains intrinsically disordered and conformationally dynamic. Above a critical RNA concentration, these ribonucleoprotein complexes rapidly and cooperatively assemble into large nucleocapsid-like particles, wherein the individual HCVncd subunits become substantially more extended. [Display omitted] •What role does the core protein play in nucleocapsid-like particle (NLP) assembly?•The core protein is highly dynamic and unstructured in the absence of RNA.•A small, dynamic ribonucleoprotein complex forms at low RNA concentrations.•At high RNA concentrations, these ribonucleoprotein complexes assemble into NLPs.•The core protein adopts an expanded structure within the oligomeric NLPs.